Effects of commonality in transaction contracts and their provisions – Comparative Jurisprudence Study – - Al-Ghazi, Shamsul Alam Mohammed Fayaz (Journal of Islamic Sciences, 2021)
This research deals with the rule of benefiting from the common share and its effects on transaction contracts; this research has been presented in five sections. In the first, I explained the commons and its causes with mentioning their types. In the second, I knew the effects of commonality in companies and demonstrated the dispute of jurists regarding the requirement of communality in the profit of the company. The third came indicating the effects of common property in mortgage, including the doctrine of the jurists in that and their evidence and what was mentioned in the discussions, indicating the most correct saying of the scholars. On the fourth, I explained the provisions of common lease between two partners. The fifth section included the doctrines of jurists in the endowment of one of the partners share of the public domain, explaining the evidence of jurists in that and what was mentioned in the discussions and indicated the most correct in it; then it was concluded with a conclusion that included the most important results and recommendations.
Keywords: the communal; the effects of communion; the communal mortgage; the communal leasing between partners; the effects of commonality in the endowment